Notes on the history of Portuguese anesthesiology: the doctoral thesis of Francisco Luis Gomez (1823 –1874) - Bleck, João Duarte (Journal of the Portuguese Society of Anesthesiology, 2016)
“De l’Étherisation, Considerée sous les Rapports Théorique et Pratique” (“The etherisation considered under theoretical and practical views”) is the title of the thesis that Francisco Luis Gomez presented and public defended to obtain the doctorat at the Montpellier University. The thesis is divided in 5 chapters: Chapitre Premier – Considérations générales sur la sensibilité et la douleur; Chapitre Deuxième – Des moyens mis en usage afin d’éviter la douleur aux maladies soumis aux opérations chirurgicales; Chapitre Troisième – Des théories relatives à l’éthérisation; Chapitre Quatrième – Indications et contre-indications des inhalations d’éther; Chapitre Cinquième – Fluide et instruments propres aux inhalations d’éther; suites des inhalations. The present paper studies the different chapters as they reflect medical, philosophical and university concepts of the middle of the 19th century